Tropical Root and Tuber Crops Cassava, Sweet Potato, Yams And Aroids - Lebot, Vincent (CABI, 2014)
Vegeculture, tropical food production based on vegetatively propagated energy crops, probably emerged before agriculture based on cereals and grains. The tropical root and tuber crops (cassava, sweet potato, yams and aroids) are among the oldest on earth. In many areas, especially in the wet tropics, they were the only staples and fed extensive populations before the introduction of cereals. Today, they represent the second most important set of food crops in developing countries, closely following the cereals. They are produced with low inputs but are an important source of income and employment in marginal areas, especially for women. Consumed mostly by the poorest, they contribute greatly to food security and are held in high esteem culturally. They are also cash crops and are used for animal feed or as raw material for industrial processing.